Identification of a putative novel polycyclic aromatic hydrocarbon-biodegrading gene cluster in a marine Roseobacteraceae bacterium Sagittula sp. MA-2 - Mayuko Abe; Miharu Sakai; Robert A. Kanaly; Jiro F. Mori (Microbiology Spectrum)
ABSTRACT The ability to biodegrade polycyclic aromatic hydrocarbons (PAHs) and the catabolic enzymes responsible for PAH biotransformation in marine bacteria belonging to the family Roseobacteraceae remain largely unexplored despite their wide distribution and highly diverse physiological traits. A bacterial isolate within Roseobacteraceae originating from coastal seawater, Sagittula sp. strain MA-2, that biotransformed phenanthrene and utilized it as a growth substrate was found to possess a putative PAH-degrading gene cluster on one of the eight circular plasmids in its genome. Subsequent comprehensive investigations utilizing bacterial genomes in public databases revealed that gene clusters potentially homologous to this newly found cluster are widely but heterogeneously distributed within Roseobacteraceae and a few non-Roseobacteraceae (Paracoccaceae and Rhizobiaceae) strains from saline environments. Catabolic functions of the enzymes encoded in strain MA-2 were predicted through the profiling of phenanthrene biotransformation products by liquid chromatography-electrospray ionization high-resolution mass spectrometry and substrate docking simulations using predicted three-dimensional structures of selected proteins, and phenanthrene biodegradation pathways were proposed. Strain MA-2 appeared to biodegrade phenanthrene via two separated, concurrent pathways, namely the salicylate and phthalate pathways. This study serves as the first investigation into the functional genes potentially responsible for PAH biodegradation conserved in Roseobacteraceae bacteria, expanding scientific understanding of the physiological repertoire evolved in this ubiquitous marine bacterial group.IMPORTANCEThe ocean is often characterized as the terminal destination for persistent polycyclic aromatic hydrocarbon (PAH) environmental pollutants; however, the ability to biodegrade PAHs and the corresponding enzymes conserved among marine bacteria are less understood compared to their terrestrial counterparts. A marine bacterial isolate, Sagittula sp. strain MA-2, belonging to the family Roseobacteraceae—a widely distributed and physiologically diverse marine bacterial group—was found to possess a functional gene cluster encoding enzymes potentially responsible for PAH biodegradation in its genome and exhibit the ability to biodegrade the three-ring PAH, phenanthrene. Intriguingly, gene clusters potentially homologous to this cluster were also distributed broadly across genomes from different Roseobacteraceae genera in public databases, which has not been previously investigated. The knowledge provided here expands our understanding of the physiology of Roseobacteraceae and may be applied to explore biotechnologically useful bacteria that contribute to the remediation of polluted marine environments or high-salinity wastewater.